2021
DOI: 10.3390/molecules26154689
|View full text |Cite
|
Sign up to set email alerts
|

Doubly Decarboxylative Synthesis of 4-(Pyridylmethyl)chroman-2-ones and 2-(Pyridylmethyl)chroman-4-ones under Mild Reaction Conditions

Abstract: The doubly decarboxylative Michael–type addition of pyridylacetic acid to chromone-3-carboxylic acids or coumarin-3-carboxylic acids has been developed. This protocol has been realized under Brønsted base catalysis, providing biologically interesting 4-(pyridylmethyl)chroman-2-ones and 2-(pyridylmethyl)chroman-4-ones in good or very good yields. The decarboxylative reaction pathway has been confirmed by mechanistic studies. Moreover, attempts to develop an enantioselective variant of the cascade are also descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The synthesis of chromanones and bicyclic compounds primarily relies on harnessing the reactivity of 3-carboxylic acid coumarins, which is governed by their intrinsic decarboxylation potential. Albrecht et al reported a doubly decarboxylative Michael type addition of pyridyl acetic acids (111) to coumarin 3-carboxylic acids (110), providing access to interesting 4-(pyridylmethyl) chroman-2-ones derivatives (112), bearing two bioactive heterocyclic scaffolds (Bojanowski and Albrecht, 2021). The process has been conducted under Brønsted base catalysis, specifically N-methyl morpholine (NMM), in THF at room temperature and many substituents were well-tolerated during the transformation, including electron-withdrawing groups, electron-donating groups, and bulky aromatic rings (Scheme 6-path a).…”
Section: -Carboxy Coumarinsmentioning
confidence: 99%
“…The synthesis of chromanones and bicyclic compounds primarily relies on harnessing the reactivity of 3-carboxylic acid coumarins, which is governed by their intrinsic decarboxylation potential. Albrecht et al reported a doubly decarboxylative Michael type addition of pyridyl acetic acids (111) to coumarin 3-carboxylic acids (110), providing access to interesting 4-(pyridylmethyl) chroman-2-ones derivatives (112), bearing two bioactive heterocyclic scaffolds (Bojanowski and Albrecht, 2021). The process has been conducted under Brønsted base catalysis, specifically N-methyl morpholine (NMM), in THF at room temperature and many substituents were well-tolerated during the transformation, including electron-withdrawing groups, electron-donating groups, and bulky aromatic rings (Scheme 6-path a).…”
Section: -Carboxy Coumarinsmentioning
confidence: 99%
“…In 2021, a similar study for depicting the enhancement of the condition was developed by Bojanowski and co-workers, where 0.5 M N-methyl morpholine was used as a base and THF as a solvent at room temperature for 20 hours. [37] In 2014, Shao and co-workers developed catalyst-free tandem Michael addition/decarboxylation of coumarin-3-carboxylic acid 1 with Indole 73 (Scheme 17). [38] According to the study of plausible mechanism, Michael's addition reaction was observed, where the electrophilicity of alkene in coumarin-3carboxylic acid precisely works due to the carboxylic acid group and lactone moiety.…”
Section: C-3 Substituted Coumarin-3-carboxylic Acidmentioning
confidence: 99%
“…Notably, no product was obtained on reaction with 2‐benzyl pyridine and other sterically hindered substrates due to steric hindrance. In 2021, a similar study for depicting the enhancement of the condition was developed by Bojanowski and co‐workers, where 0.5 M N‐methyl morpholine was used as a base and THF as a solvent at room temperature for 20 hours [37] …”
Section: C‐4 Substitution Of Coumarin‐3‐carboxylic Acidmentioning
confidence: 99%